Disparity in Occupational Health Risk During the Pandemic: Potential Misestimation and Its Implications for Health Policies. Issue 10 (9th October 2022) - Yuan, Bocong; Lan, Junbang; Li, Jiannan
Abstract : Policymakers should be aware of misunderstanding of occupational risk brought by simple dichotomy of essential and non-essential occupations. There are potential overestimation of risk faced by some essential occupations and underestimation of risk faced by some non-essential occupations during the pandemic. Abstract : Objective: This study clarifies potential misestimation of occupational risk caused by the dichotomy of frontline essential and nonessential occupations in prior studies. Methods: The linear regression is used to investigate the occupational risk in terms of incidence rate, hospitalization, and mortality on community level during the pandemic. Results: Overall, frontline essential occupations were positively associated with incidence rate, hospitalization, and mortality (156.06, 18.47, and 3.49; P < 0.01). Among essential occupations, however, education, training, and library occupations were negatively associated with them, whereas transportation, protective service, food preparation, and serving occupations were insignificantly associated with them. Moreover, among nonessential occupations, building and grounds cleaning, construction, and extraction occupations were positively associated with them. Conclusion: The dichotomy of frontline essential and nonessential occupations can bring overestimation and underestimation of occupational risk during the COVID-19 pandemic.